2(2y+7)-9y=-2(3-5y)+5

Simple and best practice solution for 2(2y+7)-9y=-2(3-5y)+5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(2y+7)-9y=-2(3-5y)+5 equation:


Simplifying
2(2y + 7) + -9y = -2(3 + -5y) + 5

Reorder the terms:
2(7 + 2y) + -9y = -2(3 + -5y) + 5
(7 * 2 + 2y * 2) + -9y = -2(3 + -5y) + 5
(14 + 4y) + -9y = -2(3 + -5y) + 5

Combine like terms: 4y + -9y = -5y
14 + -5y = -2(3 + -5y) + 5
14 + -5y = (3 * -2 + -5y * -2) + 5
14 + -5y = (-6 + 10y) + 5

Reorder the terms:
14 + -5y = -6 + 5 + 10y

Combine like terms: -6 + 5 = -1
14 + -5y = -1 + 10y

Solving
14 + -5y = -1 + 10y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-10y' to each side of the equation.
14 + -5y + -10y = -1 + 10y + -10y

Combine like terms: -5y + -10y = -15y
14 + -15y = -1 + 10y + -10y

Combine like terms: 10y + -10y = 0
14 + -15y = -1 + 0
14 + -15y = -1

Add '-14' to each side of the equation.
14 + -14 + -15y = -1 + -14

Combine like terms: 14 + -14 = 0
0 + -15y = -1 + -14
-15y = -1 + -14

Combine like terms: -1 + -14 = -15
-15y = -15

Divide each side by '-15'.
y = 1

Simplifying
y = 1

See similar equations:

| 10+6x=46 | | 2x+7=14+5x | | 16=3x+3 | | 100/5/2*5=16 | | 8x+9=2(7x-6) | | 13*4-22/11+5*x=75 | | 40+3x=-20 | | (3+w)w+w+(3+w)=24 | | 2x-5=34+x | | 7(c-9)=9(2c-8)+4 | | iman=5 | | 3x^2-6x-5=4 | | 12-5u= | | 3x^4-4x^2-1=0 | | lg(2x+40)=1.75 | | 8x+3(20-x)=125 | | 57.50-8=49.50 | | a+1/2=1 | | 731848618382638+7782658236472634972347692= | | 2(x-1)+10x=5(2x+3)+4 | | factorx^2-3x+1=0 | | x^2+2*(k-3)*x+(k-1)=0 | | 4(2x+5)+9v=36 | | 4x-8-2x=2(x-4) | | ax+b=2x | | A+3=b | | 7x+4=-x+-10 | | k+3.91=287 | | 4Y-8=3Y-4 | | 5x^4-3x^2=0 | | 22-7=3a | | 12.45=g+4g |

Equations solver categories